Planification stratégique et asymétries territoriales. Grenoble et le Grand Genève, deux régions urbaines alpines à l’épreuve de la cohérence. - Nathalie Bertrand; Dominik Cremer-Schulte; Mathieu Perrin (Revue de Géographie Alpine)
Territorial cohesion is today a guiding principle of spatial planning, especially at city region scale. Given the extension of city region perimeters, the relationships between cities, outskirts and rural areas could undergo a renewal. The objective of this article is to show that governance processes in the framework of strategic spatial planning projects tend to reveal, or even to maintain, disparities between urban and peripheral territories, especially in mountain areas. Their capacities to influence the territorial projects turn out to be unequal, as territories do not have the same resources (financial, social, human and institutional capitals). On the basis of spatial planning documents and interviews, the article analyses two alpine city region planning initiatives, Greater Geneva and Grenoble city region.